Comorbidities in children with Down syndrome: experience in a tertiary care hospital of Bangladesh - Zabeen, Fahmida; Mohsin, Fauzia; Jesmin, Eva; Mahbuba, Sharmin; Hassan, M Quamrul (BIRDEM Medical Journal, 2021)
Background: Down syndrome or trisomy 21 is one of the most common chromosomal disorders with moderate intellectual disability. In addition to mental retardation, this syndrome is associated with different congenital anomalies and characteristic dysmorphic features. Affected individuals are more susceptible to congenital heart disease and digestive anomalies, pulmonary complications, immune and endocrine system disorders. While several international studies have shown association of co-morbidities with trisomy 21, there is insufficient data available in Bangladesh.The present study aimed to evaluate the associated co-morbidities in children with Down syndrome. Methods: A cross-sectional study was conducted among pediatric cases with Down syndrome who attended the endocrine outpatient department (OPD) of BIRDEM General Hospital from June 2006 to December 2016. The cases were diagnosed either by Karyotyping or by characteristic phenotypes.The clinical and laboratory data of the patients were collected from outpatient history records for analysis. Results: There were total 42 children with Down syndrome, with mean age 4.2 years at assessment and female predominance (1.47:1). Thyroid dysfunction was the most common (69%) followed by congenital heart disease (57%). Among the thyroid disorders, acquired hypothyroidism was found in 55% cases, congenital hypothyroidism in 41% cases and only one had hyperthyroidism. Isolated patent ductus arteriosus (PDA) and atrial septal defect (ASD) comprised the commonest single congenital heart disease found in 53% and combined atrioventricular septal defect was the commonest among complex congenital cardiac defect observed in our study. Both thyroid dysfunction and congenital heart disease were found more in female children with Down syndrome than their male counterpart and it was found statistically significant. Fifty percent of our Down syndrome cases were referred from other healthcare centers to address developmental delay. Conclusion: Hypothyroidism and congenital heart disease are frequently associated in Down syndrome children in Bangladesh. This calls for developing awareness among health professionals to diagnose comorbidities at an early stage and to form recommendations for long term follow up. BIRDEM Med J 2021; 11(3): 191-196